Dermoid and epidermoid cysts of the mouth: Clinicopathological and cytokeratin profile - Schitini-Junior, Osvaldo Schitini; Henriques, Aguida Cristina Gomes; Freitas, Valéria Souza; Gurgel, Clarissa Araújo; Cury, Patrícia Ramos; Souza, Lélia Batista; Santos, Eliabe Almeida dos; Azevedo, Roberto Almeida De; Silva, Viviane Palmeira da; Santos, Jean Nunes dos (Journal of Oral Diagnosis, 2019)
Introduction: The mechanisms of cell differentiation and pathogenesis in oral epidermoid cysts and dermoid cyst is poorly know. Objective: To report clinicopathological features and investigate cytokeratin profile of oral epidermoid cysts and dermoid cyst. Material and Methods: Eight cases of epidermoid cysts, 4 of dermoid cyst, and 2 Fordyce granules were included. For analysis of the immunohistochemical expression of cytokeratins (6, 7, 8, 10, 13, 14, 18 and 19), brown staining in the sections examined were defined as positive considering three layers: superficial, intermediate and basal. Results: In dermoid cyst, cytokeratins 7, 8, 9 and 19 were expressed in one case. Cytokeratin 6 was detected in six cases of epidermoid cysts. Cytokeratins 10, 13 and 14 were expressed in all cysts. Cytokeratin 18 was absent in all cysts. Cytokeratins 10 and 14 was observed in Fordyce granules. Cytokeratin 10 was more expressed in peripheral cells and immature sebaceous glands. As these glands became more differentiated, cytokeratin 10 was not detected, while cytokeratin 14 was expressed in mature sebocytes. Cytokeratins 10, 13 and 14 were expressed in the lining mucosa adjacent to Fordyce granules, similar to normal oral mucosal lining. Conclusion: cytokeratin profile is altered in dermoid cyst and epidermoid cysts compared to lining oral mucosa.